2009
DOI: 10.1111/j.1360-0443.2009.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing heavy alcohol use in adolescents (PAS): cluster randomized trial of a parent and student intervention offered separately and simultaneously

Abstract: AimsTo evaluate the effectiveness of two preventive interventions to reduce heavy drinking in first-and second-year high school students. Design and setting Cluster randomized controlled trial using four conditions for comparing two active interventions with a control group from 152 classes of 19 high schools in the Netherlands. Participants A total of 3490 first-year high school students (mean 12.68 years, SD = 0.51) and their parents. Intervention conditions (i) Parent intervention (modelled on the Swedish Ö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
1
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(196 citation statements)
references
References 28 publications
8
177
1
10
Order By: Relevance
“…Additionally, students in the intervention condition reported a significantly greater reduction in alcohol-related consequences relative to students in the control group. These findings are consistent with the growing body of research indicating web-based interventions are effective in reducing drinking and alcohol-related consequences in adolescents (Koning et al, 2009;Newton et al, 2009;Schwinn et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Additionally, students in the intervention condition reported a significantly greater reduction in alcohol-related consequences relative to students in the control group. These findings are consistent with the growing body of research indicating web-based interventions are effective in reducing drinking and alcohol-related consequences in adolescents (Koning et al, 2009;Newton et al, 2009;Schwinn et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…The web-based interventions used in these studies were also lengthy, including 4 -12 modules or sessions, with each session taking up to 40 minutes. Additionally, only two of these studies evaluated a school-based program (Koning et al, 2009;Newton et al, 2009). School-based interventions have several potential advantages over clinic-based interventions (Wagner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. have achieved a major shift in the consensus' on effects of advertising bans, citing Saffer & Dave [8] and Saffer & Chaloupka [9]. The first study ignores other alcohol policies, so the effect of advertising bans is statistically biased [10].…”
Section: Alcohol Marketing Policy: the Missing Evidencementioning
confidence: 99%
“…Finally, rather than adopting a one-sided search for reasons why this trial failed to replicate the effects identified in the first study, we point to the need for an independent evaluation which takes into account the total evidence base of all three studies. Meta-analytical procedures and the thorough assessment of risk of bias in the initial study, as well as in the two subsequent trials [1,8] would improve the basis for the effect estimates, and provide guidance on the degree of confidence to place in them.…”
mentioning
confidence: 99%